A Rare Case of Coexisting Breast Cancer and Refractory Acute Myeloid Leukemia. (25th August 2020) - Ballotta, L.; Trisolini, S. M.; Iori, A. P.; La Rocca, U.; Micozzi, A.; Gentile, G.; De Giacomo, T.; Guarini, A.; Foà, R.; Capria, S.
Abstract : The occurrence of acute myeloid leukemia (AML) within six months from a diagnosis of breast cancer (BC) is rarely reported in the literature, and it is associated with a poor prognosis. We report herein the case of a 40-year-old woman referred to our centre affected by BC and simultaneous AML. The patient proved refractory to first line therapy and achieved complete remission (CR) with a clofarabine-based regimen followed by allogeneic stem cell transplantation (ASCT). Both during salvage chemotherapy and after ASCT, the patient presented severe infectious complications ( acute cholecistytis and Nocardia pneumonia, respectively) treated with surgery, and currently she is alive in CR for both diseases after 29 months of follow-up. The case highlights the importance of a diagnostic assessment of any unexplained cytopenia in association with solid neoplasia under treatment, underlining the feasibility and priority of a timely treatment of the haematological neoplasm in order to achieve long-term survival.